Assessment of regeneration potential of Hibiscus sabdariffa L. under established ecosystems in Cameroon (2012)
Hibiscus sabdariffa is a non-timber-forest-plant (NTFP) that has the potential of producing fibers good in paper-making. Germination and growth potentials of H. sabdariffa under farmland, fallowland, plantation and forest ecosystems were studied. Seeds of H. sabdariffa were sown to assess germination percentage, germination rate, germination time and velocity coefficient on established plots of each ecosystem. Seedlings were randomly selected to measure growth and yield parameters of height, diameter, leaf number, fresh and dry weights. Data were subjected to ANOVA and means separated by LSD at P = 0.05. Values of germination percentage for fallowland (17.5) were significantly different from those of farmland (19.4) and plantation (19.1) ecosystems, while natural forest (18.9) had an interactive significance with farmland, plantation and fallowland. There was no significant difference between germination times among the ecosystems, but the coefficient velocity and rate of germination among the ecosystems were significantly different. There was a significant variation in growth and yield values among the ecosystems. However, only seedlings on farmland and fallowland survived with a survival rate of 96 to 86%, respectively. H. sabdariffa can thus, be sustainably regenerated on farmland and fallowland ecosystems for the extraction of stem fibres for paper-making